THE ONLINE CATALOGUE AT THE UNIVERSITY OF GUELPH LIBRARY: THE PROPOSED SYSTEM ARCHITECTURE - Ridley, Michael (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF